Análisis de las aptitudes físicas de los alumnos de la carrera de cultura física y deportes período 2013/2014 - Villavicencio Saez, Yeferson Aurelio (2015)
This thesis refers to the analysis of the physical skills of students in the career of physical culture and sports period 2013 / 2014.Tiene as a scientific problem How to contribute with a set of physical tests in students of physical culture and race sports to enable their academic performance in the period 2013-2014. General objective is aimed at determining the physical skills and academic achievement in students of the School of Physical Culture and Sports. Different methods that allowed us to guide us throughout the process of research such as the scientific method, the inductive applied - deductive, logical historical, analysis synthesis among others, the population for the analysis of this research consists of 54 students from the career of Physical Culture at the National University of Loja. The type of study is descriptive qualitative: it allows describing the phenomenon in all its entirety, it has a pre experimental design since working with one group and applies a borrow and posttest, which facilitates the evaluation of the alternative proposal two very important categories treated the physical skills and the development of physical abilities, the conclusions I have reached are as follows. In the physical test push-up, endurance, abdominals, speed, Long Jump without momentum, flexibility, students evaluated not reach on average 50% of them located in the first level of the test applied, so it becomes necessary implement a test system to verify its initial state, final and intermediate for all modules of the race.